Perceived Body Image, Eating Behavior, and Sedentary Activities and Body Mass Index Categories in Kuwaiti Female Adolescents - Lemia H. Shaban; Joan A. Vaccaro; Shiryn D. Sukhram; Fatma G. Huffman (Hindawi Limited, 2016)
Background. The State of Kuwait has a growing obesity epidemic in both genders and all age groups; however, obesity rates in the young seem to be rising. Methods. We conducted a cross-sectional survey in 169 Kuwaiti female adolescents attending both private and public schools spanning the six governorates in the State of Kuwait in order to explore female adolescents' self-image, body dissatisfaction, type of school (private versus public), TV viewing, and computer games and their relationship to body mass index. Results. Approximately half the students classified as obese perceived their body image to lie in the normal range. Females in the obese category were the most dissatisfied with their body image, followed by those in the overweight category. Eating behavior, level of physical activity, school type, television viewing, computer/video usage, and desired BMI were not significantly associated with level of obesity. Conclusion. This study was one of the few studies to assess adolescent females' body image dissatisfaction in relation to obesity in the State of Kuwait. The results suggest that including body image dissatisfaction awareness into obesity prevention programs would be of value.